Psychopathology and executive functions in cocaine addicts - García-Fernández, Gloria; García-Rodríguez, Olaya; Secades-Villa, Roberto; Sánchez-Hervás, Emilio; Fernández-Hermida, José Ramón (Anales de Psicología / Annals of Psychology, 2012)
The aim of this study was to assess the presence of psychopathological symptoms in a sample of cocaine addicts and to examine the relationship between these symptoms and neuropsychological performance on executive functioning tasks. Fifty treatment-seeking outpatients for cocaine addiction participated. The EuropASI, the SCL-90-R, the BDI and a neuropsychological protocol, comprising different tasks sensitive to the detection of alterations in different components of the executive functions, were collected for each subject at the beginning of treatment. Results showed that at least 26% of the sample scored above the psychopathological risk cutoff of the dimensions of the SCL-90-R and 81.6% showed depressive symptoms at treatment entry assessment. Only a higher level of depression and phobic anxiety were associated with attentional difficulties and information processing speed. There were no significant associations between other psychopathological dimensions and neuropsychological test performance scores.